Expert system for safe application of pesticides to control insect pests in orchard - WU Jia-lun; GAO Song; LI Li-qing (浙江大学学报. 农业与生命科学版, 2003)
An expert system for safe application of pesticide in orchard is developed, which includes the risk assessment of pesticides after employing to orchard. This is a ruler-based system. Accord to the dialogue of user-computer, user can obtain some solutions for their problems, such as identifying of insect pests, decision making for using pesticide to control insect pest, forecasting the development of insect pests on orchard and so on. Under the condition of using pesticides, the system will use risk assessment model to evaluate and rank available pesticides so as to direct user how to safe application of pesticides.